A nontargeted study of muscle proteome in severely obese women with androgen excess compared with severely obese men and nonhyperandrogenic women. Issue 3 (March 2016) - Insenser, María; Montes-Nieto, Rafael; Martínez-García, M Ángeles; Escobar-Morreale, Héctor F
Abstract : Objective: Androgen excess in women is frequently associated with muscle insulin resistance, especially in obese women with polycystic ovary syndrome. However, whether this is a primary event or the result of indirect mechanisms is currently debated. Design: This is an observational study. Methods: We obtained skeletal muscle biopsies during bariatric surgery from severely obese men ( n =6) and women with ( n =5) or without ( n =5) androgen excess. We used two-dimensional differential gel electrophoresis and matrix-assisted laser desorption/ionization-time-of-flight/time-of-flight mass spectrometry to identify muscle proteins showing differences in abundance between the groups of obese subjects. Results: Women with hyperandrogenism presented the lowest abundances of glycogen phosphorylase, pyruvate kinase, β-enolase, glycerol-3-phosphate dehydrogenase, creatine kinase M-type, and desmin, whereas the abundances of these molecules were similar in control women and men. Conclusion: According to our nontargeted proteomic approach, women with hyperandrogenism show a specific alteration of the skeletal muscle proteome that could contribute to their insulin resistance. Because men do not show similar results, this alteration does not appear to be the direct effect on muscle of androgen excess, but rather the consequence of indirect mechanisms that merit further studies.